Characterization of familial breast cancer in Saudi Arabia. (December 2015) - Merdad, Adnan; Gari, Mamdooh; Hussein, Shireen; Al-Khayat, Shadi; Tashkandi, Hana; Al-Maghrabi, Jaudah; Al-Thubaiti, Fatma; Hussein, Ibtessam; Koumosani, Taha; Shaer, Nehad; Chaudhary, Adeel; Abuzenadah, Adel; et al.
Abstract Background The contribution of genetic factors to the development of breast cancer in the admixed and consanguineous population of the western region of Saudi Arabia is thought to be significant as the disease is early onset. The current protocols of continuous clinical follow-up of relatives of such patients are costly and cause a burden on the usually over-stretched medical resources. Discovering the significant contribution of BRCA1/2 mutations to breast cancer susceptibility allowed for the design of genetic tests that allows the medical practitioner to focus the care for those who need it most. However, BRCA1/2 mutations do not account for all breast cancer susceptibility genes and there are other genetic factors, known and unknown that may play a role in the development of such disease. The advent of whole-exome sequencing is offering a unique opportunity to identify the breast cancer susceptibility genes in each family of sufferers. The polymorphisms/mutations identified will then allow for personalizing the genetic screening tests accordingly. To this end, we have performed whole-exome sequencing of seven breast cancer patients with positive family history of the disease using the Agilent SureSelect™ Whole-Exome Enrichment kit and sequencing on the SOLiD™ platform. Results We have identified several coding single nucleotide variations that were either novel or rare affecting genes controlling DNA repair in the BRCA1/2 pathway. Conclusion The disruption of DNA repair pathways is very likely to contribute to breast cancer susceptibility in the Saudi population.